ANALISIS TRANSFORMASI HARTA ILEGAL OLEH PEWARIS DALAM PERSPEKTIF HUKUM WARIS ISLAM: STUDI KASUS PENADAH BARANG CURIAN - M. Iqbal; Ilmi, Muhammad Bahrul; Hamdani, Almanna Fikri; Chesio, Muhammad Rafli; Dalimunthe, Fitri Zalita; Tari, Rizki Kurnia (YUSTISI, 2025)
In Pulau Rakyat District, precisely in Asahan Regency, there is a mother who is the principal of an elementary school. This mother turned out to be a receiver of stolen goods, which is indicated by people who often find lost chickens or ducks in their homes. Then this mother had a new strategy, where she only received stolen goods from outside the village so that other people would not find out. Then, the money from receiving stolen goods was used to buy land. Later this mother died, by her child (the heir) the assets left by the mother are now used to build houses for poor children and those who are still relatives. This research was conducted to understand that charity is one form of effort as much as we can to clean our assets and return the rights of others because the assets we do not know the owners of. This research uses a qualitative approach, the data taken is primary data that comes directly from the surrounding community. The results of this research show the application of the principle "Man Ikhtalatho Bimalihi Al-Halalu Wal Haromu Akhroja Qadarha Al-Haromi Wal Baqii Halalu Lahu" (whoever has mixed halal with haram, he must take out the amount of haram, then what is left becomes halal for him) which in its application must give charity to assets whose owners we do not know or assets obtained through haram means. This discussion certainly cannot be separated from the theory of tafriq al-halal an al-haram.